2013
DOI: 10.1371/journal.pone.0057395
|View full text |Cite|
|
Sign up to set email alerts
|

The Proteome of Human Liver Peroxisomes: Identification of Five New Peroxisomal Constituents by a Label-Free Quantitative Proteomics Survey

Abstract: The peroxisome is a key organelle of low abundance that fulfils various functions essential for human cell metabolism. Severe genetic diseases in humans are caused by defects in peroxisome biogenesis or deficiencies in the function of single peroxisomal proteins. To improve our knowledge of this important cellular structure, we studied for the first time human liver peroxisomes by quantitative proteomics. Peroxisomes were isolated by differential and Nycodenz density gradient centrifugation. A label-free quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 47 publications
(72 reference statements)
4
91
0
1
Order By: Relevance
“…2, A and B). Notably, subcellular distribution as well as spectral count-based quantification of peroxisomal proteins in this study are comparable to the data reported for peroxisomes isolated from human liver tissue (Gronemeyer et al, 2013a). ZOOM fractionation before 1-DE allowed us to detect 26 additional peroxisomal proteins that were undetected in T1 and T2, including two new peroxisomal proteins later verified in this study (see below), and therefore significantly improved the coverage of the peroxisomal proteome (Fig.…”
Section: One-dimensional Gel Electrophoresis Followed By Liquid Chromsupporting
confidence: 86%
“…2, A and B). Notably, subcellular distribution as well as spectral count-based quantification of peroxisomal proteins in this study are comparable to the data reported for peroxisomes isolated from human liver tissue (Gronemeyer et al, 2013a). ZOOM fractionation before 1-DE allowed us to detect 26 additional peroxisomal proteins that were undetected in T1 and T2, including two new peroxisomal proteins later verified in this study (see below), and therefore significantly improved the coverage of the peroxisomal proteome (Fig.…”
Section: One-dimensional Gel Electrophoresis Followed By Liquid Chromsupporting
confidence: 86%
“…In support of a similar role in metazoans, ATAD1 has recently been found on peroxisomes (23,24) and mitochondria (25). In contrast to these similarities, ATAD1 in mouse brains has been suggested to regulate synaptic plasticity and learning by downregulating postsynaptic AMPA receptors (26), indicating that Msp1 homologs may also have been coopted in evolution for other specialized functions.…”
Section: Discussionmentioning
confidence: 98%
“…Several lines of evidence point to the presence of a FAO-like complex within peroxisomes. The activity of an alcohol:NAD + oxidoreductase has been detected in peroxisomes (Sakuraba and Noguchi 1995) but more recently, proteomic analyses of peroxisomes from human and rat tissues identified alcohol dehydrogenase 1A (ADH1A) as a FADH with a PTS1-containing signal (Islinger et al 2007;Gronemeyer et al 2013). These observations suggest that peroxisomes possess the capability to metabolize fatty alcohols back to fatty acids, but further functional studies need to be performed.…”
Section: Fatty Alcohol Metabolismmentioning
confidence: 99%